Christopher Williams - Kölnische Dramaturgie - McDonough, Tom 1969- (Verlag der Buchhandlung Walther und Franz König, 2023)
Latest book on the work of American photographer, Christopher Williams. Williams is a Professor at the Art Academy, Dusseldorf and lives and works in Cologne and Chicago. He has been represented by David Zwirner gallery since 2000. The book features a text from writer and critic, Tom McDonough
Keywords: Williams, Christopher -- 1956-; Fotografie; Christopher Williams; Köln; Zeitgenössische Kunst; Künstlerbuch